2020
DOI: 10.1021/acschembio.0c00676
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics Contribute to Substrate Selectivity and Catalysis in Human Kynureninase

Abstract: Kynureninases (KYNases) are enzymes that play a key role in tryptophan catabolism through the degradation of intermediate kynurenine and 3′-hydroxy-kynurenine metabolites (KYN and OH-KYN, respectively). Bacterial KYNases exhibit high catalytic efficiency toward KYN and moderate activity toward OH-KYN, whereas animal KYNases are highly selective for OH-KYN, exhibiting only minimal activity toward the smaller KYN substrate. These differences reflect divergent pathways for KYN and OH-KYN utilization in the respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Beyond epitope mapping, HDX-MS continues to be utilized for studying protein–protein interactions in complex protein systems and revealing mechanisms of activation in a range of systems including: clotting factors, 320 , 327 329 metabolic enzymes, 67 , 298 , 330 338 heat shock proteins 317 , 339 , 340 and other chaperones, 341 348 signaling complexes, 349 360 and complexes exclusively residing in membranes. 361 HDX-MS has also been extensively used to study interactions between proteins with nucleic acids, including activation of transcription factors.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond epitope mapping, HDX-MS continues to be utilized for studying protein–protein interactions in complex protein systems and revealing mechanisms of activation in a range of systems including: clotting factors, 320 , 327 329 metabolic enzymes, 67 , 298 , 330 338 heat shock proteins 317 , 339 , 340 and other chaperones, 341 348 signaling complexes, 349 360 and complexes exclusively residing in membranes. 361 HDX-MS has also been extensively used to study interactions between proteins with nucleic acids, including activation of transcription factors.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…Beyond epitope mapping, HDX-MS continues to be utilized for studying protein–protein interactions in complex protein systems and revealing mechanisms of activation in a range of systems including: clotting factors, , metabolic enzymes, ,, heat shock proteins ,, and other chaperones, signaling complexes, and complexes exclusively residing in membranes . HDX-MS has also been extensively used to study interactions between proteins with nucleic acids, including activation of transcription factors. Other notable applications are the characterization of ligands with weak affinity such as metals , or carbohydrates. , For proteins with multiple distinct ligand binding sites, it has been shown that by performing a concentration series it is possible to characterize individual interactions. , The strength of HDX-MS to provide detailed insight into such a wide range of interactions continues to drive its use to study increasingly complex biological systems.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…Taken together, our data demonstrate that by rational selection of suitable arginine and lysine residues for mutagenesis, PEGylation efficiency and consistency can be significantly improved while preserving the catalytic activity post-PEGylation. Our experimentally-validated rational PEGylation design may be applicable and benefit other protein and enzyme therapeutic molecules including asparaginase (Karamitros and Konrad, 2016;Meneguetti et al, 2019), cysteinase (Cramer et al, 2017) and kynureninase (Triplett et al, 2018;Karamitros et al, 2020).…”
Section: Pegylation Optimization Of Hstpmentioning
confidence: 99%
“…Determination of kinetic parameters. The steady-state specific activity assays were carried out, as reported previously 5,12 . In short, we mixed 20 µL of enzyme in DPBS buffer with 80 µL of L-KYN (Sigma-Aldrich) at 37 °C.…”
Section: Preparation Of Kynureninasesmentioning
confidence: 99%
“…All four putative KYNases we selected show comparable or even substantially higher kinetic parameters than Pf-K 5,12 (Fig. 2b, Supplementary Fig.…”
mentioning
confidence: 97%